Secure Message Communication Protocol Among Vehicles in Smart City - Dua, Amit; Kumar, Neeraj; Das, Ashok Kumar; Susilo, Willy (IEEE transactions on vehicular technology, 2018)
Secure messages exchange among different vehicles is one of the most challenging tasks in future smart cities. Any malicious activity has the potential to compromise the confidentiality, integrity, and authenticity of messages exchanged between different vehicles. To ensure secure message communication among the vehicles in a smart city environment, a novel scheme using elliptic curve cryptographic (ECC) technique has been presented in this paper. For this purpose, a two-level authentication key exchange scheme has been designed. In the first level authentication, \text{CH} s are verified by series of messages exchanged between \text{CH} s and the \text{CA} . The verified \text{CH} s are responsible for authentication of vehicles in the second level authentication, followed by exchange of messages between \text{CH} and vehicle. The security analysis using widely accepted Burrows-Abadi-Needham logic, formal security analysis using random oracle model and verification using the widely known automated validation of Internet security protocols and applications (AVISPA) tool, and also the informal security analysis have been done with respect to various types of attacks. Moreover, a comparative analysis of the proposed scheme with existing related schemes reveals that it generates low overhead and latency, and high reliability during messages exchange between vehicles and the \text{CA} .